(untitled) (The Peerian Journal, 2022)
In the article, the issues of modernization of the content of taught modules and raising the efficiency of education to a new level of quality are reflected in the article. It describes the technologies developed by the authors for the practical training classes taught in this system. Key words: innovation, educational technology, pedagogical process, management, development.